Effect of mesenchymal stem cell-derived exosomes on the inflammatory response after stroke - Ozal Beylerli; Ilgiz Gareev; Huaizhang Shi; Tatiana Ilyasova (Brain Hemorrhages)
Stroke, characterized by sudden onset and significant mortality rates, represents a critical challenge in effectively treating neuroinflammation to improve treatment efficacy. In this context, mesenchymal stem cell (MSC)-derived exosomes have attracted significant attention in scientific research due to their diverse cellular origin, tiny size, and huge number of bioactive molecules. Recent studies have shed light on the remarkable potential of MSC-derived exosomes to not only suppress the inflammatory responses of microglia and astrocytes, but also enhance their neuroprotective functions. Moreover, these exosomes have demonstrated a remarkable ability to modulate various immune cells and inflammatory mediators, thereby exerting profound mitigating effects on neuroinflammation. Through a thorough examination of the role and underlying mechanisms of MSC-derived exosomes in mitigating neuroinflammation after stroke, this review aims to provide comprehensive information and recommendations for the development of innovative therapeutic strategies aimed at significantly improving the treatment of stroke.